Association between triglyceride-glucose index and sarcopenic obesity in adults: a population-based study - Zhao, Zhengmei; Cai, Ruiting; Tao, Lili; Sun, Yuxiao; Sun, Keping (Frontiers in Nutrition, 2025)
BackgroundSarcopenic obesity is characterized by the coexistence of sarcopenia and obesity, which has been demonstrated to be linked to insulin resistance. The triglyceride-glucose (TyG) index is a novel surrogate indicator of insulin resistance. However, the relationship between sarcopenic obesity and the TyG index remains unclear. This population-based study aimed to investigate the association between TyG index and sarcopenic obesity in adults.MethodsThis study utilized data from the China Health and Retirement Longitudinal Study (CHARLS), individuals aged over 45 years were categorized into sarcopenia, obesity, sarcopenic obesity, and control groups. Baseline characteristics were analyzed across these groups. Logistic regression models were employed to explore the association between the TyG index and sarcopenic obesity, adjusting for confounding variables. Subgroup analyses were conducted to explore the potential variations in this association across different demographic and clinical variables.ResultsA total of 9,485 individuals were included in the study, with the sarcopenic obesity group exhibiting a higher TyG index (8.96 ± 0.61) compared to other groups (p < 0.001). A significant and independent association was observed between higher TyG index and increased likelihood of sarcopenic obesity, even after adjusting for confounders. Participants in the highest TyG index tertile had a 1.82-fold increase in the risk of sarcopenic obesity compared to those in the lowest tertile. Subgroup analyses revealed significant associations between TyG index and sarcopenic obesity across various demographic and clinical variables, particularly in individuals aged over 60 years, females, and those with chronic diseases.ConclusionThe findings suggest a strong association between elevated TyG index and sarcopenic obesity in adults, independent of demographic and clinical factors. Further large-scale prospective studies are warranted to validate and expand upon these findings.